MINDFULL GROUP SEBAGAI UPAYA PENINGKATAN PSYCHOLOGICAL WELL BEING ANAK BROKEN HOME DAN SINGLE PARENT DI DESA PURWODADI - Vebrina, Dinda; Putra, Edysyah; Pranata, Anzas (Institut Pendidikan Tapanuli Selatan, 2025)
Psychological well-being is an individual's perception of their life experiences. Well-being is the basis of life and the standard for enjoying life. If an individual's well-being is not good, he will judge himself as bad. His life experience is bad, his way of assessing life is bad, his motivation to change his life is also bad (Bradburn, 1998). One of the factors that influences psychological well-being is social support which is defined as a sense of comfort, attention, appreciation or perceived help. by an individual obtained from various sources, including partners, family, friends, coworkers, and social organizations (C. D Ryff, 1989). The presence of social support can foster feelings of being loved (Ermayanti & Abdullah, 2007), appreciated, cared for, and as part of a social network, such as a community organization within the individual. The term Psychological well-being is a term for welfare. Based on observations we made in Purwodadi Village, Batunadua District, Padangsidimpuan City, there are 1,016 residents consisting of 482 male residents, 534 female residents, of which there are 238 male heads of families, and 83 female heads of families, 8 male orphans, 7 female orphans, 19 male children separated, 35 female separated, and 6 female separated and divorced. This shows that many children are dependent on single parent family heads